2000
DOI: 10.1507/endocrj.47.451
|View full text |Cite
|
Sign up to set email alerts
|

Development of Embryos in Superovulated Guinea Pigs following Active Immunization against the Inhibin .ALPHA.-Subunit.

Abstract: Abstract.Embryo recovery and subsequent embryonic development from guinea pigs treated with or without Inhibin vaccines were compared to determine the effect of active immunization against the inhibin a-subunit. Twenty female guinea pigs of the Hartley strain were injected 3 times either with 1 ml inhibin vaccine (recombinant ovine inhibin a-subunit in oil emulsion: 50 ,ig/ml, inhibin-immunized group), or 1 ml placebo (saline in oil emulsion; control group) at 4 week intervals. After one estrous cycle followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Multiple ovulations have been induced successfully by passive immunization against endogenous inhibin in several species such as mice [27], rats [28], hamsters [29], cows [30,31], mares [32], and goats [33]. Furthermore, several studies have shown that oocytes superovulated with immunization against inhibin have the ability to develop normally [27,31,34,35], suggesting that inhibin immunization could be applicable to a wide range of animal species. Although Rivier and Vale [28] reported that increased numbers of pups were obtained after immunoneutralization of inhibin in rats, detailed analysis on embryo quality during peri-implantation was not conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple ovulations have been induced successfully by passive immunization against endogenous inhibin in several species such as mice [27], rats [28], hamsters [29], cows [30,31], mares [32], and goats [33]. Furthermore, several studies have shown that oocytes superovulated with immunization against inhibin have the ability to develop normally [27,31,34,35], suggesting that inhibin immunization could be applicable to a wide range of animal species. Although Rivier and Vale [28] reported that increased numbers of pups were obtained after immunoneutralization of inhibin in rats, detailed analysis on embryo quality during peri-implantation was not conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Dev. 48: [599][600][601][602][603][604][605] 2002) t is reported that immunoneutralization of inhibin to induce superovulation provides an alternative to current follicle stimulating hormone (FSH) or equine chorionic gonadotropin (eCG) t r eat m en t pr o t o c o ls fo r t h e pr o d uc t i o n o f transferable embryos in mammals [1][2][3][4][5][6][7][8]. Several studies have shown that active immunization of heifers against inhibin α-subunit [9-13] and passive…”
mentioning
confidence: 99%
“…Although several studies have described how passive immunization against inhibin can enhance follicular developments and ovulation rates in mammals [7][8][9][10], there are as yet no reports on ovarian localization of inhibin antibody. We recently showed that active immunization against the inhibin α-subunit results in an increase in the ovulation rate [6,11,12] and passive immunization against the inhibin α-subunit in the luteal phase results in an increase in the number of small follicles, and plasma FSH in the guinea pig [13,14]. Nevertheless, whether passive immunization against inhibin can increase the ovulation rate and affect follicular development in the follicular phase in guinea pigs has not been documented.…”
mentioning
confidence: 99%